Properties and Roles of γδT Cells in Plasmodium yoelii nigeriensis NSM Infected C57BL/6 Mice - Xie, Hongyan; Xie, Shihao; Wang, Mei; Wei, Haixia; Huang, He; Xie, Anqi; Li, Jiajie; Fang, Chao; Shi, Feihu; Yang, Quan; Qi, Yanwei; Yin, Zhinan; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Many kinds of immune cells are involved in malaria infection. γδT cells represent a special type of immune cell between natural and adaptive immune cells that play critical roles in anti-parasite infection. Methods In this study, malaria infection model was constructed. Distribution of γδT cells in various immune organs and dynamic changes of γδT cells in the spleens of C57BL/6 mice after infection were detected by flow cytometry. And activation status of γδT cells was detected by flow cytometry. Then γδT cells in naive and infected mice were sorted and performed single-cell RNA sequencing (scRNA-seq). Finally, γδTCR KO mice model was constructed and the effect of γδT cell depletion on mouse T and B cell immunity against Plasmodium infection was explored. Results Here, splenic γδT cells were found to increase significantly on day 14 after Plasmodium yoelii nigeriensis NSM infection in C57BL/6 mice. Higher level of CD69, ICOS and PD-1, lower level of CD62L, and decreased IFN-γ producing after stimulation by PMA and ionomycin were found in γδT cells from infected mice, compared with naive mice. Moreover, 11 clusters were identified in γδT cells by scRNA-seq based t-SNE analysis. Cluster 4, 5, and 7 in γδT cells from infected mice were found the expression of numerous genes involved in immune response. In the same time, the GO enrichment analysis revealed that the marker genes in the infection group were involved in innate and adaptive immunity, pathway enrichment analysis identified the marker genes in the infected group shared many key signalling molecules with other cells or against pathogen infection. Furthermore, increased parasitaemia, decreased numbers of RBC and PLT, and increased numbers of WBC were found in the peripheral blood from γδTCR KO mice. Finally, lower IFN-γ and CD69 expressing CD4+ and CD8+ T cells, lower B cell percentage and numbers, and less CD69 expressing B cells were found in the spleen from γδTCR KO infected mice, and lower levels of IgG and IgM antibodies in the serum were also observed than WT mice. Conclusions Overall, this study demonstrates the diversity of γδT cells in the spleen of Plasmodium yoelii nigeriensis NSM infected C57BL/6 mice at both the protein and RNA levels, and suggests that the expansion of γδT cells in cluster 4, 5 and 7 could promote both cellular and humoral immune responses.